Forest products, livelihoods and conservation: case studies on non-timber forest product systems. volume 2 - Africa - Sunderland, Terry C.H.; Ndoye, O. (Center for International Forestry Research, 2004)
This book contains 17 case studies of non-timber forest products (NTFPs) in Africa. it reveals an ancient system of resources moving through space and time, resources which further enable African people benefit from their marketing capacity locally. As these case studies show, establishing or strengthening markets for NTFPs can help to encourage renewable resource conservation and can contribute significantly to rural livelihoods. However, for NTFP extraction to 'save' large tracts of forests will have to be resolved, just as it must be resolved if eco-tourism, selective logging or any other economic activity is to be conducted in an environmentally sound manner. In addition, attempts to raise the market value of NTFPs, and therefore rural incomes, could be self-defeating if agricultural production of these products originally harvested from the wild is the result. In addition, understanding the political economy is crucial in addressing the economic, social and isntitutional contexts in which NTFPs are harvested and traded. The report are organized to present a standard set of information to support comparative analysis, but the authors also included each detail, idocyncracies and analyses of issues and opportunities in their own cases. Individually, the cases provide a wealth of interesting and useful information.